Report of Committee on Urban Wastes Report—Part I and Appendices—Part II - Planning Commission (Planning Commission, 1975)
The collection and disposal of refuse and other wastes is one of the pressing problems of city life which has assumed great importance. With the growing urbanisation as a result of planned economic growth and industrialisation, it is becoming acute and calls for immediate and concerted action. The proper disposal of urban wastes has not only the dimension of preservation and improvement of public health to it but it has great utility and value for agriculture purposes as well.
Government of India, Ministry of Works and Housing